Casimir effect for the scalar field under Robin boundary conditions: a functional integral approach - de Albuquerque, L. C.; Cavalcanti, R. M. (Iop Publishing Ltd, 2004)
In this work we show how to define the action of a scalar field such that the Robin boundary condition is implemented dynamically, i.e. as a consequence of the stationary action principle. We discuss the quantization of that system via functional integration. Using this formalism, we derive an expression for the Casimir energy of a massless scalar field under Robin boundary conditions on a pair of parallel plates, characterized by constants c(1) and c(2). Some special cases are discussed; in particular, we show that for some values of cl and c(2) the Casimir energy as a function of the distance between the plates presents a minimum. We also discuss the renormalization at one-loop order of the two-point Green function in the philambda(4) theory subject to the Robin boundary condition on a plate.